Open Educational Resources in Universidad Estatal a Distancia (Revista Electrónica Calidad en la Educación Superior, 2018)
This article pretends to evidence the work of the Universidad Estatal a Distancia from Costa Rica with the Open Educational Resources (OER): the beginning, the process, achievements and the actual challenges. To do so we are going to start putting the OER in the international and national context to show the institutional need of adapt this kind of resources to the educational process. Further we are going to present the path and the efforts made to expand the use, adaptation and creation with OER in different disciplines and the results that were obtained until the present moment. Finally, we are going to mention the actual challenges of the university and how can deal with them, to make patent the invitation to work with this kind of resources.